Assessment of Surface Glycan Diversity on Extracellular Vesicles by Lectin Microarray and Glycoengineering Strategies for Drug Delivery Applications (Small Methods 2/2022). Issue 2 (17th February 2022) - Shimoda, Asako; Miura, Risako; Tateno, Hiroaki; Seo, Naohiro; Shiku, Hiroshi; Sawada, Shin‐ichi; Sasaki, Yoshihiro; Akiyoshi, Kazunari
Abstract : Back Cover In article number 2100785, Akiyoshi and co‐workers assessed surface glycan diversity on extracellular vesicles (EVs) using an evanescent field fluorescence‐assisted lectin microarray. This is a useful technique not only for highly sensitive determination of EV surface glycans but also profiling EV heterogeneity. Moreover, glycoengineered EVs can control cell‐EV interactions for drug delivery applications.